KRITISASI BANK SYARIAH TERHADAP PEMBIAYAAN SEKTOR PERTANIAN DI SULAWESI SELATAN - Syathir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
The phenomenon of world's interest toward Islamic banking is not only concerned on fiqih muamalah but also on its economic potential as an alternative economic system that has been existed before but has not been able to provide welfare through the societies. South Sulawesi, for instance, as a province which has massive land for agriculture should be able to contribute greatly to inhabitants. Inattentions is the main constraint particularly of banking sector. Hence, to maximize that potency, Islamic banking have to make a strategic alliance to create a partnership with microfinance foundation like Baitul mal wa tamwil in order to get equal expansion, that is conducted by islamic banking, even for underdeveloped communities.